Bioequivalence trial of diclofenac: effects of Eudragit and tablet preparation, formulation characterization, release profiles, and bioavailability measurements - Kecman, Sanja (PONS - medicinski časopis, 2018)
Abstract The study aimed to evaluate the effects of changing excipients including type of Eudragit polymer, on release and absorption profiles in vitro and in vivo, of tablets containing the antiinflammatory drug, diclofenac. Formulation 1 consisted of diclofenac tablets containing Eudragit L30, and Formulation 2 consisted of diclofenac tablets containing Eudragit L100, and both formulations contained different excipients. Tablets were assessed, in vitro, for weight, hardness, diameter, thickness, mass uniformity, disintegration and dissolution profiles and drug content. Tablets were also assessed in vivo by gavage in healthy rabbits and assessing diclofenac plasma concentrations and pharmacokinetic parameters. Results showed that in vitro analyses demonstrated non-equivalence while in vivo analyses demonstrated equivalence. This suggests that although different types of Eudragit and excipients modulated the in vitro dissolution and release profiles of diclofenac, in vivo absorption in rabbits remained similar representing bioequivalence.